Development of a novel formulation with hypericin to treat cutaneous leishmaniasis based on photodynamic therapy in in vitro and in vivo studies (2015)
ABSTRACT:An evaluation of the leishmanicidal activity in vitro and in vivo of hypericin, an expanded-spectrum photosensitizer found in Hypericum perforatum, is presented. Hypericin was evaluated against intracellular amastigotes in vitro of Leishmania (Viannia) panamensis. A topical formulation containing 0.5% hypericin was developed and assayed in vivo in a hamster model of cutaneous leishmaniasis. Results demonstrate that hypericin induces a significant antiamastigote effect in vitro against L. panamensis by decreasing the number of parasites inside infected cells. The topical formulation of 0.5% hypericin allows healing of L. pana- mensis-induced lesions upon a topical application of 40 mg/day plus visible-light irradiation (5 J/cm2, 15 min), twice a week for 3 weeks.